2008
DOI: 10.1097/brs.0b013e31816054f8
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Model of Reduced Nucleus Pulposus Glycosaminoglycan Content in the Rat Lumbar Intervertebral Disc

Abstract: Study Design-An in vivo model resembling early stage disc degeneration in the rat lumbar spine.Objective-Simulate the reduced glycosaminoglycan content and altered mechanics observed in intervertebral disc degeneration using a controlled injection of chondroitinase ABC (ChABC).Summary of Background Data-Nucleus glycosaminoglycan reduction occurs early during disc degeneration; however, mechanisms through which degeneration progresses from this state are unknown. Animal models simulating this condition are esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 41 publications
1
43
0
Order By: Relevance
“…Rabbit lumbar 76,80–83 and rat caudal discs 8487 have been used extensively, although other animal models exist. 85,86 Both physical injury, such as stab wound 6,88 or controlled needle puncture, 89,90 and chemical degradation 83–87 approaches have been used.…”
Section: Intradiscal Therapeutics: Animal Studiesmentioning
confidence: 99%
“…Rabbit lumbar 76,80–83 and rat caudal discs 8487 have been used extensively, although other animal models exist. 85,86 Both physical injury, such as stab wound 6,88 or controlled needle puncture, 89,90 and chemical degradation 83–87 approaches have been used.…”
Section: Intradiscal Therapeutics: Animal Studiesmentioning
confidence: 99%
“…Transanular approaches have been used to inject enzymatic agents for chemonucleolysis in several animal species, 17,34 -42 including rodents. [43][44][45] It has been suggested that digestion of proteoglycans induces nucleus pulposus (NP) depressurization and loss of tensional stress in the AF, resulting in altered disc mechanics 17,35,46,47 and, consequently, degeneration. Another approach has been partial or full anular stab injury, also performed in a variety of species.…”
mentioning
confidence: 99%
“…16,[23][24][25][26] Lately, proteolytic enzymes including chymopapain, trypsin and papain, and chondroitinase ABC have been used for various applications. 16 This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction.…”
Section: Discussionmentioning
confidence: 99%